Resolved Hepatitis B: Achieved or Imaginary Wellbeing? - S. N. Batskikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Assessment of the clinical impact of previous hepatitis B infection (PHB).Key points. PHB is characterized by the presence of viral DNA in the organism (including intrahepatic cccDNA and integrated DNA). Possible virus persistence in the PHB patient's hepatocytes potentiates the agent transmission risk via haemotransfusion, organ transplantation and haemodialysis. Occult HBV infection in PHB individuals can reactivate at background immunosuppressive or chemotherapies. PHB with chronic liver diseases of various aetiology significantly rises the risk of cirrhosis and hepatic cancer. The PHB association with autoimmune liver diseases and extrahepatic gastrointestinal cancer needs a careful research to confirm the possible involvement of hepatitis B virus in morbid genesis.Conclusion. No clinical signs of acute or chronic disease, HBsAg clearance and negative viral DNA load in blood of PHB individuals do not necessarily imply a complete disease eradication.PHB elicitation improves accuracy of the overall prognosis, reduces the virus transmission risk and prevents the reactivation of HBV infection.